Strategy Formulation for Start-up and Small Business Travel Agency in Bandung - Veryadesa, Ananto; Yudoko, Gatot (The Indonesian Journal of Business Administration, 2014)
Abstract—the number of travel agencies were increasing align with the increasing number of tourists in Indonesia. In 2012, there were 3,342 of travel agents in Indonesia, where 200 of them are located in West Java Province (APHI, 2012). Several big players of travel agent are primarily making travel arrangement for business trip and company tours. There are also small business player, including start up, where most of them are categorize as the majority of travel agent in Indonesia. They also offer travel arrangement except they are most likely targeting the retail customer. To sustain in the business, a start-up and small business travel agency should formulate a strategy to differentiate their products and services with other competitors. The study case was taken in Bandung city, where three travel agents selected. They are Prima Riau Holiday (PRH) Bandung, Seruni Tour & Travel and Fly Bandung. Research gathering was based on secondary data and one on one interview with management of the travel agents. Kepner-Tregoe method was used to analyze the situation, problem and decision. In formulating strategy, the business model was used to create the 9 building blocks from value proposition to cost structure and revenue stream. The business model analysis were based on internal and external environment analytical score review of Strategic Factor Analysis Summary (SFAS). Based on the SFAS scoring, travel agent should become specialist for tour or travel package, where they could provide level 3.0 of tourism marketing and collaborate with 9 (nine) center of creative industry in Bandung City. In the implementation plan, the formulated strategy should be implemented in each functional level, from operational to marketing plan. Keywords: tourism, start-up, business strategy